Computed tomographic evaluation of bone tunnel enlargement following single bundle anterior cruciate ligament reconstruction with hamstring autograft - Chandrashekar, Sunil; N., Manjunath A.; S., Shivakumar M. (International Journal of Research in Orthopaedics, 2021)
The purpose of this study is to evaluate tibial and femoral tunnel diameter following single bundle anterior cruciate ligament (ACL) reconstruction and correlation between tunnel enlargement and clinical outcome. Twelve patients who underwent primary arthroscopic single bundle ACL reconstruction with hamstring graft were included in prospective case series. Preoperative clinical evaluation was performed using international knee documentation committee (IKDC) subjective score and grade, Tegner knee score and Lysholm knee score. Computed tomography (CT) evaluation of the femoral and tibial tunnels were done on post-operative day (POD) 1 and at a mean follow up of 9 months (range 7-12 months) and were compared with functional scores. Our study shows significant tibial and femoral tunnel enlargement on CT scan at 9 months (range 7-12 months) postoperatively. All the clinical evaluation scales showed improvement postoperatively. The mean average femoral tunnel diameter increased significantly (p<0.001) from 8.17±0.57 to 9.08±0.660 (10%) and tibial tunnel diameter increased significantly (p<0.001) from 8.08±0.669 to 9.07±0.601 (11%) postoperatively at a mean follow up of 9 months (range 7-12 months). No statistically significant difference between tunnel enlargement and clinical values were found. In our current prospective CT based study, we conclude use of extracortical fixation of femoral tunnel with stronger fixation of the tibial tunnel, tunnel orientation and anatomic fixation close to the joint line along with less aggressive rehabilitation protocol with use of extension knee brace may result in minimization of tunnel widening with quadrupled hamstring autograft.